"Social Media has Opened a World of 'Open communication:'" experiences of Adults with Cerebral Palsy who use Augmentative and Alternative Communication and Social Media. (2nd January 2016) - Caron, Jessica; Light, Janice
Abstract : An online focus group was used to investigate the experiences of nine individuals with cerebral palsy who use augmentative and alternative communication (AAC) and social media. Information was gathered related to (a) advantages of social media, (b) disadvantages of social media, (c) barriers to successful use, (d) supports to successful use, and (e) recommendations for other individuals using AAC, support personnel, policy makers, and technology developers. Participants primarily chose to focus on social media as a beneficial tool and viewed it as an important form of communication. The participants did describe barriers to social media use (e.g., technology). Despite barriers, all the participants in this study took an active role in learning to use social media. The results are discussed as they relate to themes and with reference to published literature.